Słońce w kaftanie bezpieczeństwa, czyli najkrótsza historia misji Chrystusa (na przykładzie Na wielkiej głębokości... Borysa Popławskiego) - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2018)
The author analyzes the surrealistic miniature At great depth... by Boris Poplavsky and believes that the poem may be understood as the shortest history of Christ’s mission. This hypo- thesis is supported both by the form and the content of the work. Potentially religious meanings are hidden behind symbolic objects and actions. Sleep, for instance, takes the place of Advent, on the one hand, and, on the other, symbolizes mental doze of the Jews who were completely unprepared for the lessons Jesus taught. The author believes that Poplavsky’s text allows to state that neither the Israelites then nor the Christians now use the unique chance given to the humanity by the new commandment of Christ, the commandment to love one’s neighbor. That fact arouses poet’s pity. That state crowns the analyzed miniature and implies the evaluation of Jesus’ earthly mission.